Resource Use Efficiency of Pig Production raised with and without Open Area during Summer Season (Indian Journal of Animal Production and Management, 2024)
A total of 20 piglets (10 castrated males and  10 females) at 3 months of age with initial body  weight of 18.94 ± 1.04 Kg were randomly subjected  to minimum limit of floor area recommendations of  housing standards (IS: 3916-1966) range of 0.9-1.8  square meter for weaner to finisher. In treatments  Tc, pigs were provided with only 0.9 m2 covered  floor area per pig without access to open area and  in control (To) with covered floor area of 0.9 m2 plus  additional equal open floor area (total 1.8 m2 per  pig). Result showed that resource use efficiency in  terms of saving of 90 % space, 41.23 % labor and  22.05 % water per pig in Tc were significantly (p
Keywords: Pigs; open area; production efficiency